2008
DOI: 10.7863/jum.2008.27.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic and Pathologic Findings of Nonpalpable Thyroid Carcinomas Detected by Ultrasonography in a Medical Screening Center

Abstract: Ultrasonographic findings suggesting malignancy should be preferentially considered as indicators for FNA, regardless of size, in nonpalpable thyroid nodules. However, extracapsular invasion and lymph node metastasis are closely related to the size of the thyroid nodule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 26 publications
4
57
1
Order By: Relevance
“…The result is generally similar to several earlier studies (Kang et al, 2004;Kim et al, 2008;Cavaliere et al, 2009;Vinayak and Sande., 2012;Wang et al, 2012;Kim et al, 2013a;Kim et al, 2013c). However, there was little standardization among authors of the vascularization pattern, which was statistically significant in present result.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The result is generally similar to several earlier studies (Kang et al, 2004;Kim et al, 2008;Cavaliere et al, 2009;Vinayak and Sande., 2012;Wang et al, 2012;Kim et al, 2013a;Kim et al, 2013c). However, there was little standardization among authors of the vascularization pattern, which was statistically significant in present result.…”
Section: Discussionsupporting
confidence: 81%
“…US is commonly used as an effective noninvasive technique for the diagnosis of benign and malignant thyroid nodules. Many scholars have focused on the valuable role of US features as predictors of malignancy (Iannuccilli et al, 2004;Kang et al, 2004;Kim et al, 2008;Lee et al, 2011;Vinayak et al, 2012;Kim et al, 2013a;Kim et al, 2013b). Currently, there is no internationally acknowledged guideline of selecting which thyroid nodules for biopsy, especially for the subcentimeter-sized ones (Iannuccilli et al, 2004;Grani et al, 2013;Kim et al, 2013a;Nixon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound (US) is an accepted standard diagnostic method for the detection of thyroid nodules worldwide (8). However, previous studies found extreme variations in the assessment of thyroid nodules by US (9)(10)(11). Conventional US has a moderate accuracy for characterizing the nature of thyroid nodules, thus supplementary diagnostic methods, including radionuclide scanning and fine-needle aspiration (FNA) biopsy, are employed for improved clinical evaluation of thyroid nodules (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…By ultrasonography, the suspicion of malignancy in a thyroid nodule may arise in the presence of hypo-reflecting nodes having inhomogeneous texture and calcifications, although these features are by no means pathognomonic [8][9][10][11][12]. It has to be kept in mind that a similar US pattern may also be observed in benign conditions, namely in longstanding infarcted goiter nodules.…”
Section: Distinction Between Benign and Malignant Vascular Lesionsmentioning
confidence: 99%